Plot-level field monitoring with Sentinel-2 and PlanetScope data for examination of sewage sludge disposal impact - Kovács, Dr., Ferenc; Ladányi, Dr., Zsuzsanna (Geographica Pannonica, 2022)
Agricultural use of sewage sludge is one of the means of sustainable environmental management. In order to monitor the short-term effects of sludge disposal a multi-year, high-resolution data collection was planned on arable land in south-eastern Hungary. Data acquisition was applied at the highest temporal and spatial resolution using Sentinel-2 and PlanetScope satellite imagery observing the vegetation period based on vegetation indices (EVI, NDVI) from 2016 to 2021. There were statistical differences in the case of sunflower and maize biomass productions but the spatial and statistical deviations between the affected and non-affected areas of sludge disposal were generally not significant. The sensitivity of EVI in the dense vegetation period and its applicability might be emphasized in a comparative analysis.
Keywords: sewage sludge, agricultural monitoring, Sentinel-2, PlanetScope, spectral index